Clinical paradigms and challenges in surface guided radiation therapy: Where do we go from here? - Batista, Vania; Meyer, Juergen; Kügele, Malin; Al-Hallaq, Hania (Radiotherapy and oncology, 2020)
Surface guided radiotherapy (SGRT) is becoming a routine tool for patient positioning for specific clinical sites in many clinics. However, it has not yet gained its full potential in terms of widespread adoption. This vision paper first examines some of the difficulties in transitioning to SGRT before exploring the current and future role of SGRT alongside and in concert with other imaging techniques. Finally, future horizons and innovative ideas that may shape and impact the direction of SGRT going forward are reviewed.